1984
DOI: 10.2151/jmsj1965.62.3_440
|View full text |Cite
|
Sign up to set email alerts
|

On the 40-50 day Oscillations During the 1979 Northern Hemisphere Summer

Abstract: Based on FGGE Level IIIb data, the structural features of 40-50 day oscillations over ann extensive region (30*S-30*N, 30*E-150*W) during the 1979 summer are detailed.The analysis confirms earlier investigations that these low frequency modes are primarily associated with the zonal wind oscillations.These 40-50 day perturbations propagate northward and eastward, which is most clearly defined over the monsoon region north of the equator from 60* to 150*E. The monsoon region is characterized by prominent spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
86
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(99 citation statements)
references
References 19 publications
(11 reference statements)
13
86
0
Order By: Relevance
“…These studies paid special attentions on the variation of the precipitation over the whole monsoon region, influence of the heating over the Tibetan Plateau on the monsoon circulation, relation between the Indian and the East Asia monsoon, moisture transport from the southern hemisphere and the 30-50 days oscillation in the monsoon (e.g., Murakami et al 1984;Tao and Chen 1987;Yanai et al 1992;Nakazawa 1992;Lau et al 1988). However, such planetary-scale aspects are not the main subjects in the present study.…”
Section: Introductionmentioning
confidence: 90%
“…These studies paid special attentions on the variation of the precipitation over the whole monsoon region, influence of the heating over the Tibetan Plateau on the monsoon circulation, relation between the Indian and the East Asia monsoon, moisture transport from the southern hemisphere and the 30-50 days oscillation in the monsoon (e.g., Murakami et al 1984;Tao and Chen 1987;Yanai et al 1992;Nakazawa 1992;Lau et al 1988). However, such planetary-scale aspects are not the main subjects in the present study.…”
Section: Introductionmentioning
confidence: 90%
“…Its relative intensity is weak as compared to the three other dominant oscillations mentioned above, and it seems to be stronger in the lower than in the upper troposphere above 500 mb level. This oscillation is better detectable in the Western than in the Central Pacific for the zonal wind, and this underlines the strong association of the ISO and the monsoon activity (Murakami and Nakazawa, 1984). Its contribution to the total fluctuations of the geopotential height is nearly the same in both parts of the Pacific Ocean.…”
Section: Spectral and Cross-spectral Analyses Of Datamentioning
confidence: 64%
“…Although they did not confirm explicitly the existence of this oscillation in the * and T data, they gave, instead, some evidence of mass flow in and out of the equatorial belt with the oscillation, showing that the meridional wind should be involved. This oscillation has been since the object of intensive studies over the Pacific and the Indian Ocean, using the FGGE-IIIb wind data (Murakami and Nakazawa, 1984), the cloudiness or the cloud wind vector (Yasunari, 1980(Yasunari, , 1981Takeda and Ikeyama,1984) or OLR (Weickmann et al, 1985).…”
Section: Spectral and Cross-spectral Analyses Of Datamentioning
confidence: 99%
“…Saha and Bavadekar (1973) using additional upper air data concluded that 70% of moisture flux from the Indian Ocean in the south accounted for the bulk of moisture needed for summer monsoon rainfall. While the importance of evaporation over the AS was suggested by Murakami et al (1984) and Ghosh et al (1978), the role of cross-equatorial flux was also emphasized by others (Cadet and Reverdin, 1981;Howland and Sikdar, 1983;Sadhuram and Ramesh Kumar, 1988). Most of these studies suggest that the cross-equatorial moisture flux provides an important source of moisture for the Indian Summer Monsoon (ISM) rainfall, although the evaporation from the AS is quite significant.…”
Section: Discussionmentioning
confidence: 99%